Continuity Analysis of Groundwater Aquifers Using Geoelectrical Vertical Electrical Sounding (VES) Method with Schlumberger Configuration in Serayu-Citanduy Road and Golf Course, Tanah Merah Village, North Samarinda District, Indonesia - Djayus; Mislan; Lepong, Piter; Himawan Sadewo, Hengky (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
This study aims to analyze the continuity of the aquifer system between the Serayu-Citanduy area and the Golf Course area in Tanah Merah Village, North Samarinda District, using the Vertical Electrical Sounding (VES) method with Schlumberger configuration. Building on previous research that compared geoelectrical mapping and sounding methods for identifying aquifer layers in the Serayu-Citanduy area, this study focuses on aquifer connectivity based on resistivity profiles and geological interpretation. The VES data collected from eight measurement points revealed significant variations in lithology and aquifer types. At the Golf Course, the surface layer consists of soil (0.8 to 2.6 m depth), overlying a thick silt layer (up to 160 m depth) and a permeable sandstone aquifer between depths of 152.7 m and 160 m. The resistivity of the sandstone aquifer is approximately 20-50 Ωm. Meanwhile, at the Serayu-Citanduy Road, the lithology is divided into five main layers, with the surface layer (0.8 to 2.5 m) followed by a silt layer (5.2 to 22.9 m) and a sandstone layer from 22.9 m to 200 m depth. The resistivity of the sandstone aquifer here is higher, ranging from 50 to 150 Ωm, and is identified as an unconfined aquifer above a shale layer. Below 100.1 m, a confined aquifer is found beneath the shale layer, with resistivity values exceeding 100 Ωm. The correlation between the VES points at the Golf Course and Serayu-Citanduy Road shows continuity between the aquifer systems despite variations in thickness. These findings provide new insights into the hydrogeology of Tanah Merah and highlight the importance of groundwater management strategies for sustainable water use in North Samarinda District.